Screening of Bacillus cereus presence in minced meat and meat products originating from Serbian retail facilities. (September 2019) - Milojevic, L; Velebit, B; Djordjevic, V; Jankovic, V; Lakicevic, B; Bajcic, A; Betic, N
Abstract: The goal of this study was to investigate the prevalence and numbers of B. cereus in minced meat and meat products. Eighty-seven meat or meat product samples were collected from different retail facilities in Serbia. Meat samples were subjected to microbiological analyses using the conventional cultural method for counting and isolation of B. cereus, confirmed by microscopic and biochemical tests. Eighty-seven samples included raw minced meat (7), semi-processed meat (60), processed meat (7) and meat products (13). The prevalence of B. cereus in the collected samples was 34.5 % (30/87). This pathogen was not isolated from raw minced meats, unlike semi-processed meat products, where it had a prevalence of 40 % (24 samples). Among processed meats, 28.6 % (2) were positive, while in meat products, the B. cereus prevalence was 30.8 % (4). We hope these results will provide better understanding of B. cereus isolated from food of animal origin in Serbia and results indicate meat and meat products might play an important role in dissemination of this pathogen through the food chain.